PENGARUH PENGGUNAAN MEDIA SOSIAL DAN DIFFERENTIATION PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA ERNI DIMSUM DI MEDAN JOHOR - Muli Rahman Kandau; Munawaroh Munawaroh (Jurnal Inovasi Penelitian, 2023)
The purpose of this study was to determine the effect of using social media on purchasing decisions for Erni Dimsum in Medan, Johor. To determine the effect of product differentiation on purchasing decisions on erni dimsum in Medan, Johor. To determine the effect of the use of social media and product differentiation on purchasing decisions on erni dimsum in Medan, Johor. This research uses quantitative method. The population used in this study were 95 respondents. The data used in this study are primary data obtained through questionnaires and observations. data processing using the SPSS 23.0 application with a significance level of 0.05. From the results tested using SPSS validity and reliability testing to get valid and reliable results, Data Analysis Techniques using the Determination (R) test through multiple linear testing states that the variables Social Media Use (X1) Product Diffrentiation (X2) and Purchase Decision (Y ) on erni dimsum in Johor field by 85% showing the use of social media and product differentiation on purchasing decisions erni dimsum. While the remaining 15% is influenced or explained by other variables not included in this research model. Based on calculations performed using SPSS 23.0, the multiple regression equation for the regression model is as follows: Y = -0.713 +0.376 x1 + 0.758 x2+ e. Social Media Usage Variables (X1) Product Diffrentiation (X2) together have a significant influence on Purchase Decisions (Y) for erni dimsum in Medan, Johor.